Structure-function relationships and modifications of cardiac sarcoplasmic reticulum Ca2+-transport - Nusier, M; Shah, A K; Dhalla, N S (Physiological research, 2021)
Sarcoplasmic reticulum (SR) is a specialized tubular network, which not only maintains the intracellular concentration of Ca2+ at a low level but is also known to release and accumulate Ca2+ for the occurrence of cardiac contraction and relaxation, respectively. This subcellular organelle is composed of several phospholipids and different Ca2+-cycling, Ca2+-binding and regulatory proteins, which work in a coordinated manner to determine its function in cardiomyocytes. Some of the major proteins in the cardiac SR membrane include Ca2+-pump ATPase (SERCA2), Ca2+-release protein (ryanodine receptor), calsequestrin (Ca2+-binding protein) and phospholamban (regulatory protein). The phosphorylation of SR Ca2+-cycling proteins by protein kinase A or Ca2+-calmodulin kinase (directly or indirectly) has been demonstrated to augment SR Ca2+-release and Ca2+-uptake activities and promote cardiac contraction and relaxation functions. The activation of phospholipases and proteases as well as changes in different gene expressions under different pathological conditions have been shown to alter the SR composition and produce Ca2+-handling abnormalities in cardiomyocytes for the development of cardiac dysfunction. The post-translational modifications of SR Ca2+ cycling proteins by processes such as oxidation, nitrosylation, glycosylation, lipidation, acetylation, sumoylation, and O GlcNacylation have also been reported to affect the SR Ca2+ release and uptake activities as well as cardiac contractile activity. The SR function in the heart is also influenced in association with changes in cardiac performance by several hormones including thyroid hormones and adiponectin as well as by exercise-training. On the basis of such observations, it is suggested that both Ca2+-cycling and regulatory proteins in the SR membranes are intimately involved in determining the status of cardiac function and are thus excellent targets for drug development for the treatment of heart disease.
Keywords: vztahy mezi strukturou a aktivitou; Heart; Sarcoplasmic Reticulum; srdce; Structure-Activity Relationship; Calcium; Myocardium; myokard; sarkoplazmatické retikulum; vápník